The military as a separate society consequences for discipline in the United States and Australia - Collins, Pauline Therese (Lexington Books, 2019)
The exercise of public power by the military in civilian Western democracies such as Australia and the United States demonstrates a tendency toward failure in responsibility for moral behavior. Pauline Collins argues that a different system of military criminal investigation and discipline outside the civilian justice system enables the military to operate like a coterie and can lead to a failure in the requisite moral standard of behavior required of military personnel and maintaining civilian institutional control. Collins argues that the justifications for separate treatment of weakens both the military standing and the practice of civilian control of the military as well as leading to an overall decline in morality and values in a democratic society
Keywords: USA -- Army; Australien -- Army; Militär; Moralisches Handeln; Disziplin; Australien; USA; Civil-military relations; Military discipline / Australia; Military discipline / United States; Power (Social sciences); Moral conditions; Sociology, Military; Military discipline; Australia; United States